The effect of acupressure on clinical stress management in nursing students: a randomised controlled study - Yıldırım, Dilek; Akman, Özlem (Elsevier Korea, 2021)
Background: Nursing students experience clinical stress frequently and severely. The application of acupressure is reported to be effective in stress management. Objectives: This study was conducted to determine the effects of acupressure on reducing the stress of nursing students in clinical practice. Methods: This study was carried out using a single-blind randomized controlled experimental design. The experimental and control groups were randomly determined by using a previously prepared randomization checklist. A Participant Information Form, VAS, and the State Anxiety Inventory were applied to all students before practice. Acupressure was performed on the HT7 point and Yintang point (EX-HN3), respectively, every five minutes for a total of 30 minutes in the experimental group. Results: The level of stress experienced by the students in the experimental group before the intervention according to VAS was 6.95 ± 1.57, and it was determined as 2.82 ± 1.94 after the third application (p < 0.05). The mean clinical stress score before the application was 46.54 ± 3.81, and after the 3rd week of application, it was 25.15 ± 5.26 (p < 0.05). It was observed that the students' stress levels decreased in all measurements made after the acupressure intervention. Conclusion: This study determined that acupressure effectively reduces the stress levels of nursing students, and it may be applied in clinical stress management.
1Department of Nursing, Faculty of Health Sciences, İstanbul Aydin University, İstanbul, Turkey -- 2Department of Nursing, İstanbul Sabahattin Zaim University Faculty of Health Sciences, İstanbul, Turkey
Keywords: Stress; Acupressure; Nursing students; Anxiety; Clinical stress management